First Presentation Acute Rheumatic Fever is Preventable in a Community Setting: A School-based Intervention. Issue 12 (December 2017) - Lennon, Diana; Anderson, Philippa; Kerdemilidis, Melissa; Farrell, Elizabeth; Crengle Mahi, Suzanne; Percival, Teuila; Jansen, David; Stewart, Joanna
Abstract : Background: Robust evidence is lacking for community initiatives to prevent first presentation acute rheumatic fever (ARF) by group A streptococcal (GAS) pharyngitis treatment. Methods: We measured the effect of introducing a sore throat clinic program on first presentation ARF into 61-year 1–8 schools with students 5–13 years of age (population ≈25, 000) in Auckland, New Zealand. The study period was 2010–2016. A generalized linear mixed model investigated ARF rate changes before and after the staggered introduction of school clinics. Nurses and lay workers treated culture-proven GAS sore throats (including siblings) with 10 days of amoxicillin. ARF cases were identified from a population-based secondary prophylaxis register. Annual pharyngeal GAS prevalence was assessed in a subset. Results: ARF rates in 5–13 year olds dropped from 88 [95% confidence interval (CI): 79–111] per 100, 000 preclinics to 37 (95% CI: 15–83) per 100, 000 after 2 years of clinic availability, a 58% reduction. No change in rate was demonstrated before the introduction of clinics [ P = 0.88; incidence risk ratio for a 1-year change: 0.98 (95% CI: 0.63–1.52)], but there was a significant decrease of first presentation ARF rates with time after the introduction of the sore throat program [ P = 0.008; incidence risk ratio: 0.61 (95% CI: 0.43–0.88)]. Pharyngeal GAS cross-sectional prevalence fell from 22.4% (16.5–30.5) preintervention to 11.9% (8.6–16.5) and 11.4% (8.2–15.7) 1 or 2 years later ( P = 0.005). Conclusions: ARF declined significantly after school-based GAS pharyngitis management using oral amoxicillin paralleled by a decline in pharyngeal GAS prevalence. Abstract : Supplemental Digital Content is available in the text.